Development Of Infographic-Based Minimum Competency Assessment Instruments For High School Students In Medan City - Mhd Ihsan Syahaf Nasution; Hafnita Sari Dewi Lubis; Yushar Tanjung; Ahmad Arif Budiman Nasution (International Journal of Educational Research & Social Sciences, 2021)
This research is an applied research which aims to develop a Minimum Competency Assessment Instrument (AKM) for History Lessons based on infographics. Making the Minimum Competency Assessment Instrument (AKM) for History Lessons based on this infographic is in order to support the government's program related to the Minimum Competence Assessment (AKM) which was launched by the government as a substitute for the National Examination (UN). In this case, the making of History Questions as a simulation for Students and Handbook of Results for History Teachers in Medan. This research was conducted in three stages of trials and involved validation of material experts and also students who assessed the language component, media aspect, learning aspect, language aspect, material aspect. The final result of the three trials is very good value. To further develop the Minimum Competency Assessment Instrument (AKM) for History Lessons based on Infographics as an Assessment for Students, especially in History Lessons